2010
DOI: 10.1057/jphp.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes as a harm reduction strategy for tobacco control: A step forward or a repeat of past mistakes?

Abstract: The issue of harm reduction has long been controversial in the public health practice of tobacco control. Health advocates have been reluctant to endorse a harm reduction approach out of fear that tobacco companies cannot be trusted to produce and market products that will reduce the risks associated with tobacco use. Recently, companies independent of the tobacco industry introduced electronic cigarettes, devices that deliver vaporized nicotine without combusting tobacco. We review the existing evidence on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
278
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(291 citation statements)
references
References 15 publications
4
278
1
8
Order By: Relevance
“…The diversity of e-cigarette device types available to consumers on the Internet and in stores is rapidly increasing, with an estimated 460 brands and 7700 flavors available as of January, 2014 (Zhu et al, 2014). Although the early e-cigarettes looked similar to conventional cigarettes and were intended to mimic cigarette smoking (Cahn and Siegel, 2011;Etter and Bullen, 2011), products have evolved and now vary in shape and size, ranging from the cigarette-like devices ("cigalikes"), to "tanks" or "mods", which are larger and usually include a refillable "tank" for e-liquid (Farsalinos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of e-cigarette device types available to consumers on the Internet and in stores is rapidly increasing, with an estimated 460 brands and 7700 flavors available as of January, 2014 (Zhu et al, 2014). Although the early e-cigarettes looked similar to conventional cigarettes and were intended to mimic cigarette smoking (Cahn and Siegel, 2011;Etter and Bullen, 2011), products have evolved and now vary in shape and size, ranging from the cigarette-like devices ("cigalikes"), to "tanks" or "mods", which are larger and usually include a refillable "tank" for e-liquid (Farsalinos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Though final consensus has not been reached (Caponetto et al, 2013;Geiss et al, 2015;Wagener et al, 2012), some studies suggest that e-cigarette products may reduce risk and offer a safer alternative (Farsalinos et al, 2014) to combustible cigarettes for consumers and people exposed to second-hand smoke (Colard et al, 2015;Czogala et al, 2013;Mcauley et al, 2012;Schripp et al, 2013) when liquid formulation and devices are adequately controlled and regulated (American Industrial Hygiene Association, 2014;Cahn & Siegel, 2011;Trehy et al, 2011). Consequently, the need to apply strict and accurate methodologies to assess e-cigarette products is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Smoke generated from combustible cigarettes and aerosols produced from e-cigarettes are composed mainly of liquid droplets because of the process of homogeneous nucleation (gas-to-liquid conversion; Cahn & Siegel 2011). Previous studies have revealed that variations in manufacturing methodology for combustible cigarettes led to droplet size distributions ranging from 0.2 to 0.9 mm (Geiss et al, 2015;Ishizu et al, 1977), which likely reflects the particular sampling and dilution methodology used.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Given the well-known harms associated with cigarette smoking, switching to e-cigarettes is likely a form of harm reduction. [11][12][13][14] However, although there is evidence that e-cigarettes may help some people reduce or even quit smoking, available prospective studies suggest that e-cigarettes are similar to NRT in that most users do not quit smoking. [15][16][17][18][19][20][21] Despite these concerns, a recent cross-sectional, retrospective study found that e-cigarette users in the general population were more likely than NRT users to have quit cigarette smoking.…”
mentioning
confidence: 99%